Ecological and Socioeconomic Factors in the Occurrence of Rabies: A Forgotten Scenario - Deepak Subedi; Deepak Chandran; Sanju Subedi; Krishna Prasad Acharya (MDPI AG, 2022)
In many third world countries, where rabies is endemic in dog populations, humans continue to be at risk of contracting the disease. Vaccination is the most effective form of prophylaxis for people, yet it often fails to adequately protect dogs. The most major implications are the costs of post-exposure prophylaxis (PEP) after an exposure occurs and the loss of human life and productivity due to early mortality from rabies (about 60,000 deaths annually). The largest rabies death tolls can be found in the world's poorest regions, where rabies vaccinations for domestic dogs are uncommon and PEP is scarce. Mass vaccination of dogs, neutering programs, patient PEP, strengthening laboratory and human resources, education and awareness, and animal and human rabies surveillance are all common methods used to prevent, control, and ultimately eradicate dog-mediated human rabies. Current rabies control initiatives, however, pay little attention to the role that ecological and socioeconomic variables play in the disease's occurrence and spread. To help better inform rabies control strategies, we address in this work the ways in which ecological and socioeconomic factors affect the occurrence and spread of rabies.